Cor triatriatum sinister: a case series - Onur Isik (Türk Kardiyoloji Derneği Arşivi, 2016)
Objective: As a highly rare congenital defect, cor triatriatum sinister represents only 0.1% of congenital cardiac anomalies. Depending on the degree of obstruction and the accompanying symptoms, cor triatriatum can be diagnosed at any age. This case series described 5 patients with cor triatriatum sinister who underwent operation. Methods: Five patients with cor triatriatum sinister were seen at our institution between 2007 and 2013. The demographic characteristics and surgical results of these patients are outlined in this retrospective review. Results: The surgical approach consists of left or right atriotomy, excision of the obstructing membrane, and repair of the associated intracardiac anomalies. After an uneventful postoperative hospital stay, all patients were discharged 5–10 days postoperatively. There were no instances of recurrent constriction after surgical treatment of the cor triatriatum membrane. Patients were followed up for a median of 4 years and were symptom free. Conclusion: In the surgical management of this easily and fully treatable congenital cardiac anomaly, it is difficult to determine which atriotomy approach is comparatively more advantageous. However, in the management of cor triatriatum sinister, priority should be given to confirmation of the diagnosis and full resection of the membrane. Thus, the surgeon should not hesitate to perform additional incisions if deemed necessary.